International differences in the risk of death from smoking and obesity: The case of the United States and Finland - Neil Mehta; Irma Elo; Sari Stenholm; Arpo Aromaa; Markku Heliövaara; Seppo Koskinen (Elsevier Ltd, 2022)
Despite much interest in the health risks associated with behavioral factors, little is known about whether individuals residing in different countries experience a different set of risks. International comparisons of the death risks from major behavioral factors can shed light on whether features of health systems and epidemiological histories modify the health effects of risky behaviors. We used nationally representative samples and mortality linkages spanning the 1971–2014 period from the United States and Finland to examine cross-national differences in the risks of death from cigarette smoking and obesity. We evaluated both current and former smoking and current and prior obesity. In 1990, the approximate midpoint of our study, the death risks from current smoking were about 55% higher in U.S. women compared to Finnish women, but similar for men in the two countries. Death risks from smoking significantly increased over the period for women in both countries and there was no parallel increase in risks among men. Death risks from obesity did not significantly differ in the two countries and no significant trend in the risks were detected in either country. Reasons for the relatively high and increasing risks from smoking among American women warrant further evaluation.